Digital Transformation in Education: Teacher Empowerment Through Online Learning Media Training and Social Media - Dwita Laksmita; Dian Fadhilawati (IJECS: Indonesian Journal of Empowerment and Community Services, 2026)
ABSTRACT The advancement of digital technology requires teachers to effectively integrate online learning media and social media into their instructional practices. However, at the primary school level, there are still limitations in digital literacy as well as a lack of integrated and sustainable training programs. This community service program (PKM) aims to empower teachers at SD Negeri Segoropuro, Pasuruan, by enhancing their competencies in utilizing digital media for teaching. The program was conducted from September to December 2025 through several stages, including needs assessment, practical training, mentoring, and evaluation. The training materials covered the use of Canva, Kinemaster, and Prezi. The results indicate a significant improvement in teachers’ understanding, skills, and confidence in integrating technology into the teaching and learning process. Practically, this program offers a needs-based training model that is applicable and easily replicable in other schools. The sustainability of the program is supported by the provision of modules, video tutorials, and continuous mentoring that encourage teachers’ independent learning. Overall, this program contributes to supporting a more adaptive and sustainable digital transformation in education.  Keywords: Digital learning media, Teacher empowerment, Digital transformation, Training, social media in education.